Effect of static mixer on optical properties of plastic injection molded parts. Issue 12 (22nd October 2022) - Shotwell, Demitri; Gim, Jinsu; Yang, Huaguang; Glas, Stefanie; Chen, Edward; Turng, Lih‐Sheng
Abstract: The effect of an in‐mold static mixer on the optical properties of polystyrene (PS) parts was explored within the injection molding process. Several mixers were assessed via simulation and molding trials to identify the mixing ability and effect on optical properties including retardation and birefringence. It was found that the static mixers within the runner could successfully mix the polymer and disrupt property distributions including temperature but that there was only a slight improvement in retardation with some of the mixer cases. The experiments and simulations showed relatively good correlation in results although there were slight differences in the trends that could be due to the experimental measurement resolution or unaccounted‐for variables between the experiments and simulations. The retardation was experimentally measured using a custom‐made polariscope using photography and image processing. These experiments indicated that the use of a static mixer within the runner system of a mold could be used for homogenizing the polymer melt after the plasticizing unit. However, its effect on improving the optical performance of injection molded parts could be offset by the melt flow downstream of the static mixer and the potential increase of residual stresses due to flow restriction, suggesting the importance of mixer location and geometry. Abstract : Static mixers are placed within the runner system of molds with the aim to improve optical part quality.